Pengaruh Fluktuasi Harga Emas Dan Strategi Promosi Penjualan Terhadap Minat Nasabah - Lindung Halomoan Art; Fauziah, Fauziah; Lutfi, Ahmad (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2023)
This study aims to determine how the effect of gold price fluctuations and sales promotion strategies on customer interest in gold instalments at BSI KCP Padang Panjang. In this study, 100 respondents, customers of gold instalment at BSI KCP Padang Panjang. Multiple regression data analysis techniques using the SPSS version 26.0. The variables are gold price fluctuations (X1), sales promotion strategies (X2) and customer interest in gold instalments (Y). The results prove that gold price fluctuations and sales promotion strategies affect customer interest in gold instalments. Judging from gold price fluctuations (X1) the value of t count> t table is 3.408> 1.66 with a sig. value of 0.000 < 0.05, sales promotion strategy (X2), has a significant effect on customer interest in gold instalments (Y), this is evidenced by the results of the T test where the value of t count> t table, 7.350> 1.66, with a sig. value of 0.000 < 0.05. Then through the simultaneous test it can be concluded that the results of F count> F table (45.766> 3.09) prove that the variable gold price fluctuations and sales promotion strategies have a significant effect on customer interest in gold instalments at BSI KCP Padang Panjang.